Brand coopetition with geographical indications: Which information does lead to brand differentiation? - Dentoni, Domenico; Tonsor, Glynn T.; Calantone, Roger; Peterson, H. Christopher (My University, 2014)
Farmers and managers marketing food products with Geographical Indications (GIs) have to play a brand coopetition game: they cooperate with each other to develop a collective GI equity, yet they compete to build their individual brand and to establish market channels. Based on an online experiment on olive oil from “Riviera Ligure” (a region in North-Western Italy) through a convenient sample, this study tests a path model to 1) analyze which types and which sources of GI information differentiate an individual brand with GI from the others; and 2) explore which psychological and demographic variables play a role on the impact of GI informationon brand differentiation. The tested path model combines elements of economic consumer theory (Lancaster, 1966) and theory of attitude formation (Fishbein, 1967; Fishbein and Ajzen, 1975). Results cannot be generalized outside the observed product and sample, yet the method is applicable by the GI food industryas a consumer research tool to set up marketing communication strategies.
Keywords: Geographical Indications (GIs); Consumer behavior; Willingness-to-pay (WTP); Brand differentiation; Path analysis; Olive oil; Food products; Marketing